Dialogic Organizing : Affirming public engagement for hope and solidarity - Steyaert, Chris; Johansson, Marjana; Janssens, Maddy; Vachhani, Sheena; Hjorth, Daniel (Organization Studies, 2025)
This special issue introduction explores dialogic organizing centred on affirming public engagement for hope and solidarity. We propose ways of retheorizing and revitalizing dialogic perspectives and practices. In so doing we take our cue a Bakhtinian understanding of dialogue; however, we suggest that it is necessary to move beyond this foundational understanding. Instead, it needs to be read in conjunction and connection with scholarship on dialogue that highlights its complexity as affective and embodied processes. After sketching how theorizing the dialogic has evolved, we set out three innovations and contributions: (1) the reconceptualization of dialogic organizing in its affective, material and embodied dimensions, which implies (2) a necessary alternative consideration of dialogic practices and relations beyond the human, and (3) how this can be realized through a turn to an affirmative politics of dialogic organizing. In keeping with this dialogic spirit, we conclude by offering an opening for continued dialogue as a community of organization studies scholars, resisting the urge to arrive at the neat certainty of conclusion, and rather colluding with the reader to end on a note of openness and anticipation.
Publisher Copyright: © The Author(s) 2025. This article is distributed under the terms of the Creative Commons Attribution 4.0 Lficense (https://creativecommons.org/licenses/by/4.0/) which permits any use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage).
Keywords: affect; affirmative politics; Bakhtin; communication; dialogic organizing; dialogue; embodied practice; materiality; more-than-human relations